The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.12928/dpphj.v16i1.4613
|View full text |Cite
|
Sign up to set email alerts
|

Job Safety Analysis and Hazard Identification of Welding Process in Semarang - JSA Method AS/NZS 4360:2004

Abstract: Background: The welding workshop in Semarang City is spread over several areas in Semarang City. There are several types of work in welding workshops, namely, cutting raw materials, assembling, welding, grinding, sanding, and painting. This study aimed to analyze occupational safety and health risks in the informal welding workshop using the JSA (Job Safety Analysis) AS/NZS 4360:2004 Risk Management method. Method: This research was conducted using semi-quantitative method with descriptive analysis. A cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(34 reference statements)
0
4
0
1
Order By: Relevance
“…The intention was to investigate common tools and equipment in these Fab Labs and relevant activities. Third, site visits were made to a Fab Lab in Yaounde, where an OHS analysis was conducted (Arifin and Octaviani, 2022) (Pramitasari et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intention was to investigate common tools and equipment in these Fab Labs and relevant activities. Third, site visits were made to a Fab Lab in Yaounde, where an OHS analysis was conducted (Arifin and Octaviani, 2022) (Pramitasari et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Arifin and Octaviani(2022) identified and evaluated ship repairment process, hull cleaning, and coatingbased on hazard identification and risk assessment using the AS/NZS 4360:2004 standardand found that basic risk consisted of five levels i.e., acceptable, priority 3, substantial, priority 1 and very high. Pramitasari et al(2022) used JSA method and AS/NZS 4360:2004 standard to analyze occupational safety and health risks in the informal welding workshop; study showed that there are 8 types of welding tasks, 21 potential hazards, and 24 health consequences in the welding process. Van Derlykeet al (2022) and Halim et al (2018) have found that proper JSA implementation is effective in preventing accidents and promoting safety behaviors.…”
Section: Risk Level In Fab Labsmentioning
confidence: 99%
“…Pada tahap welding memiliki potensi bahaya fisik akibat terpapar cahaya las, terkena percikan api las, dan menyambar benda di sekitar area yang mudah terbakar sehingga dapat menyebabkan kerusakan mata, luka bakar, kebakaran. Upaya pengendalian memakai APD yang sesuai dan menjauhkan bahan/benda yang mudah terbakar (Pramitasari et al, 2021). Selain itu, juga terdapat bahaya ergonomi karena posisi tubuh yang salah, maka berisiko mengidap kifosis atau bungkuk sehingga tindakan pencegahannya yaitu menjaga postur tubuh tetap sempurna (Issue et al, 2023).…”
Section: Hasil Dan Pembahasanunclassified
“…Hazards identification was carried out in each work process at the Custom Garage, and the results showed that there were potential hazards that might occur in each of the physical, chemical, biological, ergonomics, and psychosocial hazards. Physical hazards in the welding process were the dangers of being pinched, scratched, hit and crushed, splashed fire, noise, electric shock, and radiation exposure (Pramitasari et al, 2021).…”
Section: Hazard Identificationsmentioning
confidence: 99%